Highly Transferable pAQU-Related Plasmids Encoding Multidrug Resistance Are Widespread in the Human and Fish Pathogen Photobacterium damselae subsp. damselae in Aquaculture Areas in the Black Sea - Vences, Ana; Abushattal, Saqr; Matanza, Xose M.; Dubert, Javier; Uzun, Ecren; Öğüt, Hamdi (Springer, 2020)
The marine bacterium Photobacterium damselae subsp. damselae is a pathogen that causes disease in diverse marine animals, and is also a serious opportunistic human pathogen that can cause fatal infections. Strains of this pathogen isolated from diseased European sea bass in aquaculture facilities in the Turkish coast of the Black Sea were found to exhibit reduced sensitivity to multiple antimicrobials. Selected representative strains were subjected to complete genome sequencing and plasmid characterization. It was found that multidrug resistant (MDR) isolates harboured large conjugative plasmids sharing part of their sequence backbone with pAQU-group plasmids, hitherto reported exclusively in China and Japan. Four new pAQU-group versions of plasmids were identified in the present study, containing distinct combinations of the resistance determinants tetB, floR, sul2, qnrVC, dfrA and strAB. Conjugative transfer of pPHDD2-OG2, a representative plasmid of 170,998 bp, occurred at high frequencies (2.2 x 10(-2) transconjugants per donor cell), to E. coli and to pathogenic P. damselae subsp. damselae and subsp. piscicida strains. Upon transfer, pPHDD2-OG2 conferred reduced susceptibility to a number of antimicrobials to the recipient strains. Comparative genomics analysis of host strains suggested that these MDR plasmids of the pAQU-group were acquired by different genetic lineages of Pdd. This study provides evidence that P. damselae subsp. damselae isolated from diseased fish constitute a reservoir for conjugative MDR pAQU-group plasmids in the Mediterranean basin, and have the potential to spread to diverse bacterial species.
Keywords: Photobacterium damselae; pAQU; MDR; Plasmid; Acquired resistance; Aquaculture